ERIC‐PCR genotyping of Pseudomonas aeruginosa isolates from haemorrhagic pneumonia cases in mink. Issue 1 (12th November 2014) - Han, Ming‐ming; Mu, Lian‐zhi; Liu, Xu‐ping; Zhao, Jing; Liu, Xiao‐fei; Liu, Hui
Abstract : Background: Pseudomonas aeruginosa is a significant pathogen of mink and the cause of haemorrhagic pneumonia, an acute fatal disease in farmed mink. Results: Among 90 P. aeruginosa isolates from haemorrhagic pneumonia in mink from 16 farms in Shandong province, China, 43 genotypes were identified by enterobacterial repetitive intergenic consensus PCR (ERIC‐PCR), with a diversity index of 0.96. The most prevalent ERIC‐PCR types were type 18, found in 16 isolates, and type 39, found in 15 isolates. Four serotypes were detected, with serotype G (55.6 per cent) being the most frequent. Conclusions: These results showed that there was a high degree of clonal diversity among mink P. aeruginosa clinical isolates in this study.